A case report of neurosyphilis coexisting with a positive MOG antibody manifested as optic neuritis - Shi, Min; Luo, Danqing; Li, Zhaoying; Li, Man; Jin, Shuoguo; Yang, Dongdong; Guo, Jun; Chen, Guo (Frontiers in Neurology, 2023)
Background: Neurosyphilis refers to an infection of the central nervous system by Treponema pallidum. The clinical manifestations of neurosyphilis are diverse, making it easy to miss or misdiagnose. Anti-myelin oligodendrocyte glycoprotein antibody-associated disease is a recently defined immune-mediated inflammatory demyelinating central nervous system disease. Few studies have reported the coexistence of the two diseases. Case presentation: This case report presents a 37-year-old male patient with neurosyphilis manifested as optic neuritis with a positive myelin oligodendrocyte glycoprotein (MOG) antibody. This patient received intravenous administration of 3.2 million units of procaine penicillin every 4 hours for two weeks, followed by a two-week intramuscular injection of benzathine penicillin. Additionally, methylprednisolone sodium succinate was administered intravenously at 1,000 mg/day, gradually reduced to 500 mg/day and 240 mg/day every three days. Subsequently, prednisone tablets at a dosage of 60 mg/day were orally administered, with a gradual reduction of 5 mg/day every three days until reaching a dosage of 30 mg/day. The patient’s visual acuity was improved after 26 days of hospitalization. However, the visual field and color vision did not. At three months of follow-up, the symptoms remained unchanged despite the patient continued taking oral prednisone tablets at a dosage of 30 mg/day. Conclusion: Neurosyphilis could be a potential triggering factor for MOGAD. In patients with neurosyphilis, it is strongly recommended to perform testing for MOG antibody along with other brain disease antibodies.